Digital Technologies, Big Data, and Agricultural Innovation - Sonka, S.T. (Springer, 2021)
Innovation in agricultural practices and food system performance is urgently needed to effectively respond to societal challenges of today and tomorrow. Expanding population, a changing climate, environmental distress, and the need for more nutritious and safe food supplies are only a few of those challenges. In response, new tools employing digital technology and big data are being developed and applied within agricultural production systems. This chapter explores the potential for the effective implementation of such tools and their prospective impact. While these tools provide the means to measure agricultural production activities as they happen, it is important to stress that adoption hinges on both technological and economic factors. The tools of digital technologies and big data are intriguing because their implementation is a key form of innovation and because the use of these technologies can foster additional innovation by making existing innovation systems even more effective.